1999
DOI: 10.1046/j.1365-2249.1999.00831.x
|View full text |Cite
|
Sign up to set email alerts
|

HLA-DMB expression by thyrocytes: indication of the antigen-processing and possible presenting capability of thyroid cells

Abstract: SUMMARYExpression of HLA class II molecules on thyrocytes is a characteristic feature of autoimmune thyroid disease and may lead the thyroid cells to present autoantigens to CD4 þ T lymphocytes. Since HLA-DM is a critical molecule in class II-restricted antigen processing and presentation, we assessed the expression of HLA-DMB, -invariant chain (Ii), class II transactivator (CIITA) and DRA in an untransformed, pure thyrocyte strain HTV-59A. Here we report that both HLA-DMB mRNA and the protein are expressed in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 46 publications
2
19
0
1
Order By: Relevance
“…HCgp39 is a secreted protein and may be endocytosed for presentation by professional APCs present in the joint. However, in some autoimmune diseases nonprofessional APC have been postulated to be involved such as the cytokineactivated thyrocytes in thyroid disease (62). Recent work has shown that IFN-␥-treated thyrocytes express HLA-DM␤, class II molecules, Ii and CIITA (62).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HCgp39 is a secreted protein and may be endocytosed for presentation by professional APCs present in the joint. However, in some autoimmune diseases nonprofessional APC have been postulated to be involved such as the cytokineactivated thyrocytes in thyroid disease (62). Recent work has shown that IFN-␥-treated thyrocytes express HLA-DM␤, class II molecules, Ii and CIITA (62).…”
Section: Discussionmentioning
confidence: 99%
“…However, in some autoimmune diseases nonprofessional APC have been postulated to be involved such as the cytokineactivated thyrocytes in thyroid disease (62). Recent work has shown that IFN-␥-treated thyrocytes express HLA-DM␤, class II molecules, Ii and CIITA (62). Thus in some circumstances, the requirement for HLA-DM may be fulfilled by nonprofessional APCs that have been activated to express the machinery of the traditional Ag presentation pathway.…”
Section: Discussionmentioning
confidence: 99%
“…In nonobese diabetic mice it has been shown that the lack of CIITA prevented diabetes despite noticeable pancreatic infiltration (82), whereas class II MHC deficiency alone was insufficient to prevent cytotoxic T-cell-mediated disease pathology in a model of lymphocytic choriomeningitis virusinduced diabetes (55). In autoimmune thyroiditis, potential interactions between CIITA and single-strand binding protein 1, a regulator of thyroid-stimulating hormone gene expression, may contribute to increased class II MHC expression (5, 81), thus allowing thyroid cell antigen presentation to T cells (143).…”
Section: Biological Significancementioning
confidence: 99%
“…In vitro experiments have shown that thyrocytes behave like antigen presenting cells and can induce lymphocyte migration . Expression of HLA DR II and the immunoglobulin Fc receptor (FcγRIIB2) has been found on the basal and apical surfaces of thyrocytes [Botazzo et al, 1983, Wu et al, 1999. The presentation of the latter antigen is dependent on the low level of androgens, which is probably connected with higher prevalence of AITD in women .…”
Section: Antigen Presentationmentioning
confidence: 99%